AFFECTING FACTORS ON THE TIMING OF THE ISSUANCE OF ANNUAL FINANCIAL REPORTS "EMPIRICAL STUDY ON THE JORDANIAN PUBLIC SHAREHOLDING COMPANIES" - AL- Shwiyat, Ziyad Mustafa M. (European Scientific Journal, ESJ, 2013)
The study aims to investigate the effect of several factors (company’s size represented by total assets, earnings per share, return on equity, return on assets, dividends per share, company’s age, cash flows from operating activities, in addition to the financial leverage of the company) on the timing of the issuance of the annual financial reports. The sample consists of (120) Jordanian public shareholding companies listed in Amman Stock Exchange (ASE) in 2012, and to achieve the objectives of the study, The study developed model by using multiple regression which included many independent variables and the timing of issuance of annual financial reports as the dependent variable. The results showed that Jordanian companies listed on the ASE delayed in reporting the annual financial period amounted to (111) days from the end of the fiscal year, and that the industrial companies need more time to issue public reports to become compared with other sectors. The results of multiple regression analysis showed also a positive correlation statistically significant between the company’s size, company’s age, financial leverage and the timing of annual financial reports of companies. There is a negative correlation statistical significance between earnings per share and the timing of issuance of the annual financial reports companies.